The Badung River Level Capacity Due to Probable Maximum Flood in Denpasar City - I Nyoman Sedana Triadi Triadi; Ketut Wiwin Andayani; Made Mudhina; IGL Made Parwita (Jurnal Ilmiah Telsinas, 2026)
The runoff coefficient in the Badung river basin changes from 0.57 to 0.71 in 2026, especially due to the conversion of rice fields into residential and commercial areas, as well as the reduction of mangrove forests and green open spaces. These changes have resulted in a significant increase in runoff and flooding in the Badung River. The Probable Maximum Flood calculated in 2000 was 485.82 m3/s, in 2026 it was 764.91 m3/s. Over the past 26 years, the Badung River has experienced a 57.45% increase in the Maximum Probable Flood. The embankment capacity upstream of Hasanuddin Bridge is 503.579 m3/s, while downstream of Hasanuddin Bridge the capacity of the Badung River embankment is 482.174 m3/s. This analysis concludes that flood conditions around Hasanuddin Street are 0.80 m above the average height of the Badung River embankment. Necessary measures in the study area include raising the Badung River embankment by 1.6 meters in flood-affected areas, normalizing the channel slope to 0.009, maintaining the area's flow coefficient at 0.71, and managing and controlling waste in the area. This treatment will increase the capacity of the Badung River in flood-affected areas to 886.360 m3/sec.